2013
DOI: 10.1371/journal.pone.0078730
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of sIL-2R Levels in B-Cell Lymphomas

Abstract: Elevated soluble interleukin-2 receptor (sIL-2R) in sera is observed in patients with malignant lymphoma (ML). Therefore, sIL-2R is commonly used as a diagnostic and prognostic marker for ML, but the mechanisms responsible for the increase in sIL-2R levels in patients with B-cell lymphomas have not yet been elucidated. We first hypothesized that lymphoma cells expressing IL-2R and some proteinases such as matrix metalloproteinases (MMPs) in the tumor microenvironment can give rise to increased sIL-2R in sera. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 39 publications
4
59
0
Order By: Relevance
“…The majority of authors have reported similar observations to those made in the present study, namely that the expression of MMPs in malignant cells, including MMP-9, is associated with unfavorable prognosis in patients with aggressive NHL, such as DLBCL [49,50,51]. Feng et al reported that the expression of MMP-9 was higher in DLBCL in clinical stage III and IV in comparison to clinical stage I and II [52].…”
Section: Discussionsupporting
confidence: 87%
“…The majority of authors have reported similar observations to those made in the present study, namely that the expression of MMPs in malignant cells, including MMP-9, is associated with unfavorable prognosis in patients with aggressive NHL, such as DLBCL [49,50,51]. Feng et al reported that the expression of MMP-9 was higher in DLBCL in clinical stage III and IV in comparison to clinical stage I and II [52].…”
Section: Discussionsupporting
confidence: 87%
“…In the setting of malignant lymphoma, no distinct correlations between the CD25 expression on B-lymphoma cells and the sIL-2R level have been observed, and most CD25-expressing cells in the tumors are T-cells (19). In the present case, the mechanism underlying the extremely elevated serum sIL-2R levels differed from that of malignant lymphoma; however, a high CD25 expression in leukemic cells may result in an extremely elevated sIL-2R level, which makes it difficult to distinguish MS from malignant lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Both (HL) and non-Hodgkin lymphoma (NHL) malignant cells have demonstrated expression of CD25 (Tesch et al, 1993;Waldmann, 2007). NHL tumours with high levels of surface CD25 expression include DLBCL (Hashimoto et al, 2013;Yoshida et al, 2013), follicular lymphoma (Yoshida et al, 2013) and peripheral T cell lymphoma including angioimmunoblastic T cell lymphoma and anaplastic large cell lymphoma (Gualco et al, 2009). Rarer diseases showing CD25 expression include Waldenstr€ om macroglobuliaemia (San Miguel et al, 2003) and systemic mastocytosis, which is defined by its CD25 expression (Lim et al, 2009).…”
Section: Cd25 Expression and Secretion In Malignant Cellsmentioning
confidence: 99%